High speed 3D overhauser‐enhanced MRI using combined b‐SSFP and compressed sensing. Issue 2 (8th March 2013) - Sarracanie, Mathieu; Armstrong, Brandon D.; Stockmann, Jason; Rosen, Matthew S.
<x xml:space="preserve">Abstract</x> Purpose Overhauser‐enhanced MRI is a promising technique for imaging the distribution and dynamics of free radicals. A key challenge for Overhauser‐enhanced MRI is attaining high spatial and temporal resolution while simultaneously limiting resonator and sample heating due to the long, high power radio‐frequency pulses needed to saturate the electron resonance. Methods The approach presented here embeds EPR pulses within a balanced steady state free precession sequence. Unlike other Overhauser‐enhanced MRI methods, no separate Overhauser prepolarization step is required. This steady‐state approach also eliminates the problem of time‐varying Overhauser‐enhanced signal and provides constant polarization in the sample during the acquisition. A further increase in temporal resolution was achieved by incorporating undersampled k‐space strategies and compressed sensing reconstruction. Results We demonstrate 1 × 2 × 3.5 mm3 resolution at 6.5 mT across a 54 × 54 × 110 mm3 sample in 33 s while sampling 30% of k‐space. Conclusion The work presented here overcomes the main limitations of Overhauser enhanced MRI as previously described in the literature, drastically improving speed and resolution, and enabling new opportunities for the measurement of free radicals in living organisms, and for the study of dynamic processes such as metabolism and flow. Magn Reson Med 71:735–745, 2014. © 2013 Wiley Periodicals, Inc.